Decomposition of efficiency in the global seed industry: A nonparametric approach. (16th December 2021) - Smart, Richard D.; Ait Sidhoum, Amer; Sauer, Johannes
Abstract : We analyzed the efficiency levels of nine of the largest commercial seed‐producing firms globally for the period 2008–2015 and assessed if there is a relationship between firm size and efficiency. We employed the nonparametric technique of data envelopment analysis (DEA) using an input‐oriented model with balanced panel data. We accounted for the assumption of time invariance of the frontier by using the DEA windows analysis technique. Aggregate mean overall technical efficiency increased by 0.8%. We decomposed these results to pure technical efficiency and scale efficiency, and found no meaningful relationship between firm size (assets) and efficiency.